PERAN AUDIT KEPERAWATAN DALAM MENINGKATKAN KUALITAS PERAWATAN MELALUI DOKUMENTASI DAN EVALUASI REKAM MEDIS - Metilda; Nisa, Nayla Chairun; Aris, Siva Silfiyana; Setiasih, Gilda Titin; Neng Afifah; Putri, Destiyani (SINERGI : Jurnal Riset Ilmiah, 2026)
The abstract is a brief summary of the entire article’s contents. The This article aims to examine the role of nursing audits in improving the quality of care through medical record documentation. The issue addressed focuses on the suboptimal quality of nursing documentation, which may affect service quality and patient safety. This study employed a literature review with a descriptive-analytical approach by analyzing twenty relevant national and international scientific articles related to nursing audits and medical record documentation. The literature was reviewed to identify the role of nursing audits, supporting and inhibiting factors, and their implications for quality of care. The findings indicate that nursing audits play a significant role in improving the completeness, accuracy, and consistency of nursing care documentation. Audit implementation accompanied by feedback, supervision, and organizational support encourages nurses’ compliance with documentation standards. Furthermore, the use of electronic documentation systems enhances the effectiveness of the audit process. In conclusion, nursing audits can serve as an effective strategy to improve the quality of nursing care when implemented continuously and supported by appropriate policies, training, and institutional commitment.